Synthesis and characterization of Mo-doped LiNi0.5Co0.2Mn0.3O2 cathode materials prepared by a hydrothermal process. Issue 4 (March 2017) - Li, Yunjiao; Su, Qianye; Han, Qiang; Li, Puliang; Li, Ling; Xu, Chunrui; Cao, Xinlong; Cao, Guolin
Abstract: The lithiated metal oxide precursor with α-NaFeO2 structure and low crystallinity prepared by a hydrothermal process is verified to be Li-Ni-Co-Mn-Mo composite oxide. The layered Li(Ni0.5 Co0.2 Mn0.3 )1- x Mo x O2 ( x =0, 0.005, 0.01 and 0.02) cathode material with high crystallinity for lithium ion batteries (LIBs) is obtained from the lithiated metal oxide precursor by heat treatment. The results of SEM and EDS mapping characterization indicate that the molybdenum is distributed in the materials homogeneously. The effects of molybdenum on the structure, morphology and electrochemical performances of the LiNi0.5 Co0.2 Mn0.3 O2 are extensively studied. According to the results of electrochemical characterizations, the Li(Ni0.5 Co0.2 Mn0.3 )0.99 Mo0.01 O2 sample exhibits the best discharge cycling performance with capacity retention of 97.0% after 50 cycles, and an excellent rate performance of 125.5 mAh·g −1 at 8C rate. The Li(Ni0.5 Co0.2 Mn0.3 )0.99 Mo0.01 O2 sample also shows a lower potential polarization, smaller impedance parameters and a larger Li + diffusion by CV and EIS analyses.